2011
DOI: 10.1016/j.colegn.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives of bedside nursing handover

Abstract: Bedside handover provides an opportunity for patients to be involved as active participants in their care. They value having access to information on an ongoing basis, and although not all choose the same level of interaction, they see their role as important in maintaining accuracy, which promotes safe, high quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
172
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(190 citation statements)
references
References 45 publications
(73 reference statements)
15
172
0
1
Order By: Relevance
“…This is most likely due to the fact that home nursing was free of charge to the inhabitants in 1998, whereas the patient charges for home help were gradually increased in the 1990s (33). The increased use of general practitioner services is consistent with figures from Statistics Norway (34). The increase in the use of outpatient specialist health services in the period from HUNT2 to HUNT3 is consistent with findings made by Sintef (35).…”
Section: Discussionsupporting
confidence: 81%
“…This is most likely due to the fact that home nursing was free of charge to the inhabitants in 1998, whereas the patient charges for home help were gradually increased in the 1990s (33). The increased use of general practitioner services is consistent with figures from Statistics Norway (34). The increase in the use of outpatient specialist health services in the period from HUNT2 to HUNT3 is consistent with findings made by Sintef (35).…”
Section: Discussionsupporting
confidence: 81%
“…9 With a patient-centered approach, patients are partners in their care with the expectation that their participation may lead to better outcomes and satisfaction. 7,8 Moving to a more patient-centered approach, many organizations have been implementing a standardized approach for nurse-to-nurse shift reporting through bedside reporting (bedside nursing handover) where the outgoing nurse provides report to the incoming nurse at the patient's bedside. 1,2,[6][7][8][10][11][12][13][14][15][16][17][18][19] Key benefits for nurses associated with bedside nursing handover include the opportunity for nurses to (1) clarify issues and ask questions to enhance the accuracy of the report, 13 (2) visualize the patient and prioritize care, 20 and (3) engage patients in their care.…”
mentioning
confidence: 99%
“…Key challenges identified with this approach include that it is not patientcentric and not necessarily safe for the patient, as pertinent information can be missed or care delayed because of the length of the shift report. [2][3][4][5][6] There is growing interest in a patient-centered approach to handover during critical episodes in the care process such as shift handovers 7,8 and other care transition points. 9 With a patient-centered approach, patients are partners in their care with the expectation that their participation may lead to better outcomes and satisfaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mental health settings, it may also have the potential to lead to conflicts on the acute psychiatric in-patient unit. Nursing bedside handover implementation has been well documented in acute wards (Kerr et al 2014;McMurray et al 2011); however, there are no studies that have reported on the implementation or evaluation of patient inclusive nursing handover in an acute psychiatric inpatient unit.…”
Section: Resultsmentioning
confidence: 99%